Impairment of T cell function in parasitic infections. - Vasco Rodrigues; Anabela Cordeiro-; Mireille Laforge; Ali Ouaissi; Khadija Akharid; Ricardo Silvestre; Jérôme Estaquier (Public Library of Science (PLoS), 2014)
In mammals subverted as hosts by protozoan parasites, the latter and/or the agonists they release are detected and processed by sensors displayed by many distinct immune cell lineages, in a tissue(s)-dependent context. Focusing on the T lymphocyte lineage, we review our present understanding on its transient or durable functional impairment over the course of the developmental program of the intracellular parasites Leishmania spp., Plasmodium spp., Toxoplasma gondii, and Trypanosoma cruzi in their mammalian hosts. Strategies employed by protozoa to down-regulate T lymphocyte function may act at the initial moment of naïve T cell priming, rendering T cells anergic or unresponsive throughout infection, or later, exhausting T cells due to antigen persistence. Furthermore, by exploiting host feedback mechanisms aimed at maintaining immune homeostasis, parasites can enhance T cell apoptosis. We will discuss how infections with prominent intracellular protozoan parasites lead to a general down-regulation of T cell function through T cell anergy and exhaustion, accompanied by apoptosis, and ultimately allowing pathogen persistence.